Fixed rate tenders and the overnight money market equilibrium - Tuomas Välimäki (Bank of Finland, 2001)
This paper presents a general equilibrium model of the determination of equilibrium in the interbank market for overnight liquidity when the central bank uses fixed rate tenders in its liquidity provision.We consider three alternative liquidity policy rules.First, the central bank may provide the bid amounts in full. Alternatively, the central bank can scale back the bid amounts pro rata with the individual bids.For the latter case, we consider two target options for the central bank: liquidity or an interest rate. We show that the expected overnight rate remains more tightly in the hands of the central bank if the full allotment procedure or a pure interest rate targeting rule is used than if liquidity targeting is used.We will also demonstrate how optimal bidding in tender operations varies considerably according to which procedure is chosen by the central bank.
URN:NBN:fi:bof-20140807320
Keywords: 330